The Effectiveness of Learning Tools of Applied Microbiology to Students Learning Outcomes and Softskill - Hasruddin Hasruddin; Mahmud Mahmud (Universitas Sebelas Maret, 2015)
This research aims to determine the effectiveness of applied-microbiology learning tools in problem-based learning to college students learning outcomes and softskill. Limited test by using one group pretest-posttest design was implemented on biology students in FMIPA UNIMED (State University of Medan) with total of sample 32 peoples. The data were collected by test, questionnaire, and observation sheet which futher analyzed by descriptive statistics. The effectiveness of the learning tools for the acquisition of learning outcomes can be calculated using the percentage technique. The findings of this study revealed about 81.25% students learning outcomes categorized as very high and 18.75% included into high category. The process of formation of college student softskill were effective in improving communication skills, work in groups, initiative, difficult to give up, and able to complete the task perfectly.Keywords: Effectiveness, Applied Microbiology, Learning Outcome, Softskill